A BRIEF HISTORY OF BEACH VOLLEYBALL (Fiep Bulletin - online, 2015)
The focus of this study was to trace the path of beach volleyball, from the recreational version of the court volleyball in the United States up to the inclusion of the modality as an official sport in the Olympic Games. In the description of the evolution of the sport we prioritized: the sports events and their repercussion in the media; the athletes who, through their careers, promote the popularization of the sport and the investment the modality received for its configuration, as a practice associated to young audiences. Within such a context we used Bourdieu (1990) as a theoretical reference, as Bourdieu provides a particular form of understanding modern sport, the manifestations which comprise the sports phenomenon and occupy a space of social practices called field and Elias(1994), who considers the appearance of the modern sport associated to the western civilization process, triggering a series of transformations in costumes and habits of individuals. Therefore we consider that modern sports can be perceived as microcosms while reflecting the structures of modern society of the macrocosms. Despite its origin from the court volleyball, beach volleyball was developed with its own characteristics. Played by a duo, with rules and different physical requirements due to the place where it is practice, it was built after the basis of a modern sport. From this theory, we consider that one of these needs would be related to the desire of players for greater independence and autonomy in their sport practice. This can be seen in the specific characteristics of the modality. We have concluded that beach volleyball is characterized as sport that allows the athlete to administrate his/her own career. The self-management capacity seems to be essential for a good performance in beach volleyball. The players administrate their careers as companies. They do not have contractual binds as in court volleyball. It is thus a structure that provides autonomy and independence to players.
Keywords: BEACH VOLLEYBALL HISTORY DEVELOPMENT